Pengaruh Tourist Experience dan Travel Motivation Terhadap Revisit Intention di Wisata Puncak Lawang - Pratama, Jefri Febrian; Wulandari, Dwi Pratiwi (Stupa, 2024)
This research was conducted because of problems related to Revisit Intention in the attraction of Puncak Lawang Tourism Object. The research purpose is to analyze the influence of tourist experience and motivation of travel on Revisit Intention at the Puncak Lawang tourist attraction. The research type is research by quantitative with a causal associative form. The research population was visitors who had visited the Puncak Lawang tourist motorcycle taxi, with a sample of 387 respondents, obtained using a purposive sampling technique. Data types use primary data and secondary data. The technique for data collection was conducted using a questionnaire with a scale of Likert which had undergone reliability and validity testing. The processed data was using SPSS 26.00. The analysis results are shown in tabular form. The research results show that tourist experience (X1) in category was sufficient with a percentage of 63.05%, Travel motivation (X2) in category was sufficient with a percentage of 66.93%, and intention to visit again is in the sufficient category and good category with a percentage of 61.75%. Based on the linear regression test F 282.734 with sig 0.000 < 0.05, the Travel Experience and Travel motivation variables jointly influence the Intention to Visit Again with the Adj value. R Squared 0.596. Travel Experience and Travel motivation have a significant effect on Intention to Visit Again by 59.6% and 40.4% by other factors